Socio-Economic and Health Status of Elderly People in Nepal - Paudel, Bhanu Bhakta (Journal of Development and Social Engineering, 2022)
Old age is the time associated with biological, psychological and social changes. This study aims to explore the socio-economic and health status among the elderly people. A cross sectional descriptive study was carried out among 136 elderly who were the received old age allowance of Kusma municipality, Parbat. Elderly of aged 60 years & above were selected for the study by cluster sampling method. The information was collected through interview scheduled by semi structured questionnaire with quantitative and qualitative methods. Focused group discussion and case study also carried out. The major part of the elderly population was in the age group of 70-75 (29.4%) and 75-80 (22.8%) years. Sixty-eight percent elderly were illiterate and majority (71.3%) has land ownership. There is no any income source of elderly except old age allowance (94.1%). The most health problem was gastric, sugar and pressure problem as found in 44.85%. Nearly two -fifth (37.5%) were suffering from physical; heart related and bone related problems. Types of family and health status of elderly are significance at 5% level of significance (Chi-square). The results of the study show that family support, and old age allowance schemes have a positive impact on the social and health status of the elderly. The government has to care for the elderly people with special provision to increase their quality of life and make their life healthy and productive.